2020
DOI: 10.1101/2020.04.24.20079012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating a Widely Implemented Proprietary Deterioration Index Model Among Hospitalized COVID-19 Patients

Abstract: Introduction:The coronavirus disease 2019 pandemic is straining the capacity of U.S. healthcare systems. Accurately identifying subgroups of hospitalized COVID-19 patients at high-and low-risk for complications would assist in directing resources.Objective: To validate the Epic Deterioration Index (EDI), a predictive model implemented in over 100 U.S. hospitals that has been recently promoted for use in COVID-19 patients. Methods:We studied adult patients admitted with COVID-19 to non-ICU level care at a larg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…There is therefore potential ambiguity about how the algorithm may perform in novel clinical settings or for detecting more rapid patient deterioration. Singh et al [ 33 ] evaluated the Epic Deterioration Index (EDI) prospectively in a population of 174 COVID-19 patients, assessing its performance for a composite outcome of requirement of ICU care, initiation of mechanical ventilation, or in-hospital death. While the EDI showed moderate discrimination for the COVID-19 with a maximum AUC of 0.76, the authors again do not examine ventilation as an individual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore potential ambiguity about how the algorithm may perform in novel clinical settings or for detecting more rapid patient deterioration. Singh et al [ 33 ] evaluated the Epic Deterioration Index (EDI) prospectively in a population of 174 COVID-19 patients, assessing its performance for a composite outcome of requirement of ICU care, initiation of mechanical ventilation, or in-hospital death. While the EDI showed moderate discrimination for the COVID-19 with a maximum AUC of 0.76, the authors again do not examine ventilation as an individual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Major differences in sampling: due to differences in the age of the patients (which we will address next); or due to exclusively including patients diagnosed by chest CT [34] (which is more sensitive than plain radiography); or excluding patients who already present in a severe condition [35][36][37][38] (because their objective is to study the progression from non-severe to severe); or limiting follow-up to a short period which does not allow to reach the outcome of interest to a signi cant proportion of included patients, [39,40] and therefore rising signi cant risk of selection bias that will be later discussed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a number of studies investigating severity [6][7][8][9][10][11][12] and mortality [8,[13][14][15][16] neutrophil and lymphocyte count, D-dimer, AST and GFR) mortality-prediction models were developed.…”
Section: Discussionmentioning
confidence: 99%
“…predictors in COVID-19 infection. Some of the studies reported that they developed scores or models for the prediction of disease severity[6][7][8][9][10][11][12]. Shi et al de ned a host risk score consisting of three parameters (age, sex, hypertension) and reported an increase in severe infection risk with the increasing score point (from 0 to 3)[12].…”
mentioning
confidence: 99%